1972
DOI: 10.1128/aac.1.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Penicillin on Penicillin Biosynthesis

Abstract: The addition of phenoxymethylpenicillin (10 mg/ml) at any time during the penicillin fermentation inhibited further accumulation of the antibiotic in broth but had no effect on growth. Benzylpenicillin, 6-aminopenicillanic acid (6-APA), and some semisynthetic penicillins also showed this effect, but penicillin N, peniciuloic acid, cephalosporin C, and 7-aminocephalosporanic acid did not limit penicillin accretion. Incorporation of radioactive precursors (cysteine, valine, and sodium phenoxyacetate) into penici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1974
1974
1984
1984

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The results suggested that the antibiotic was regulating its own synthesis but by an unkilown mechanism. A similar phenomenon was observed in the biosynthesis of penicillin by Penicilliut71 clzrysogenwn (7). Therefore, the effect of chloramphenicol on the synthesis of arylamine synthetase in Streptomyces sp.…”
Section: Repression Of Drylamine Synthetasesupporting
confidence: 72%
“…The results suggested that the antibiotic was regulating its own synthesis but by an unkilown mechanism. A similar phenomenon was observed in the biosynthesis of penicillin by Penicilliut71 clzrysogenwn (7). Therefore, the effect of chloramphenicol on the synthesis of arylamine synthetase in Streptomyces sp.…”
Section: Repression Of Drylamine Synthetasesupporting
confidence: 72%
“…However, if compartmentation exists in P. chrysogenum, it is possible that high penicillin concentrations exist in such a compartment. High levels of penicillin are also required to inhibit net penicillin synthesis in intact mycelia of P. chrysogenum (7), but this could be due to a permeation problem.…”
Section: Discussionmentioning
confidence: 99%
“…5-Chloro-l-(2,3,5-tri-0-acetyl-/9-D-ribofuranosyl)imidazole-4-carboxamidoxime (22). A mixture of 10 (5.07 g, 13.14 mmol), absolute ethanol (25 ml), and hydroxylamine (0.48 g) was refluxed over a steam bath for 1 h. More hydroxylamine (0.48 g) was added and the clear reaction solution was refluxed for a further 2 h. It was left at room temperature overnight.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the in vivo therapeutic effect of 16, a guinea pig skin infection model was used. 22 This nucleoside was formulated in either polyethylene glycol "300" or in propylene glycol (20%), 70% sorbitol (3%), and ethyl alcohol to 100 ml at a 5% (w/v) concentration.…”
mentioning
confidence: 99%